PENINGKATAN KEMAMPUAN MEMERANKAN TOKOH DRAMA DENGAN MENGGUNAKAN METODE BERMAIN PERAN DI KELAS XI IPS-1 SMA NEGERI 1 BAGAN SINEMBAH KAB. ROKAN HILIR - Wiwik Hartati (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
The purpose of this study was to determine the improvement in the ability to play drama in class XI IPS-1 Bagan Sinembah 1 High School. This research was carried out in the classroom including classroom action activities (PTK) in the form of initial reflection activities and conducting observations to identify problems that occur in the classroom, planning learning, implementing actions, observation and reflection. The findings of this CAR are: the skill to play drama in the first cycle of 5.48 increased in the second cycle to 7.88. It can be concluded that the ability to play drama students experienced an increase of 2.4, or by 2.4%. Some aspects that experience the most significant improvement are aspects of expression, appreciation and movement. With the increase in the average score of each aspect of assessment in playing drama in each cycle carried out, it can be concluded that the role playing method can improve the skill of playing drama in class XI IPS-1 in SMA 1 Bagan Sinembah.Keywords: Method, Role Playing, Drama Playing Skills